2021
DOI: 10.1016/j.electacta.2021.138846
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of cobalt from lithium-ion batteries using fluidised cathode molten salt electrolysis

Abstract: The future need to recycle enormous quantities of Li-ion batteries is a consequence of the rapid rise in electric vehicles required to decarbonise the transport sector. Cobalt is a critical element in many Li-ion battery cathode chemistries. Herein, an electrochemical reduction and recovery process of Co from LiCoO 2 is demonstrated that uses a molten salt fluidised cathode technique. For the Li-Co-O-Cl system, specific to the experimental process, a predominance diagram was developed to aid in understanding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
(7 reference statements)
0
19
0
Order By: Relevance
“…126 Whereas previous studies had demonstrated that the reduction of MOX fuels (where a mixture of plutonium and uranium oxides are pressed into a nuclear fuel pellet) was viable, none had solely considered the use of PuO 2 as a feed material. One of the reasons for not considering pure PuO 2 for this was that the processing of feed material into nuclear fuel pellets could lead to increased radiation doses for operators as a result of ingrowth of the gamma emitting daughter radionuclide 241 Am. These studies had considered different ratios of uranium and plutonium; Iizuka et al showed that using LiCl-0.5 wt% Li 2 O ensured that the materials (47 wt% U, 35 wt% Pu, 4 wt% Np)O 2 would eventually form an alloy.…”
Section: Plutoniummentioning
confidence: 99%
“…126 Whereas previous studies had demonstrated that the reduction of MOX fuels (where a mixture of plutonium and uranium oxides are pressed into a nuclear fuel pellet) was viable, none had solely considered the use of PuO 2 as a feed material. One of the reasons for not considering pure PuO 2 for this was that the processing of feed material into nuclear fuel pellets could lead to increased radiation doses for operators as a result of ingrowth of the gamma emitting daughter radionuclide 241 Am. These studies had considered different ratios of uranium and plutonium; Iizuka et al showed that using LiCl-0.5 wt% Li 2 O ensured that the materials (47 wt% U, 35 wt% Pu, 4 wt% Np)O 2 would eventually form an alloy.…”
Section: Plutoniummentioning
confidence: 99%
“…At the same time, cobalt remains in the melt regardless of the reaction conditions. There are several reports in the literature showing the effective extraction of cobalt from NaCl−CaCl 2 melts 28 and LiCl−KCl melts 29 by electrochemical extraction. This approach can be applied for the recovery of cobalt from the LiCl−KCl melts after samarium separation.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…[37][38][39][40] Therefore, both of above-mentioned pyrometallurgical and hydrometallurgical technologies are sophisticated, contaminative, inefficient, and high-cost. [41][42][43][44] These two traditional recycling routes should be considerably improved or totally substituted by more advanced strategies to well-meet the booming retired LIBs wave.…”
Section: Introductionmentioning
confidence: 99%